The personal shopper – a pilot randomized trial of grocery store‐based dietary advice. Issue 3 (15th April 2015) - Lewis, K. H.; Roblin, D. W.; Leo, M.; Block, J. P.
Summary: The objective of this study was to test the feasibility and preliminary efficacy of a store‐based dietary education intervention against traditional clinic‐based advice. Patients with obesity ( n  = 55, mean [standard deviation, SD] age 44.3[9.2] years, 64% women, 87% non‐Hispanic Black) were randomized to receive dietary counselling either in a grocery store or a clinic. Change between groups (analysis of covariance) was assessed for outcomes including: dietary quality (Healthy Eating Index – 2005 [0–100 points] ), and nutritional knowledge (0–65‐point knowledge scale). Both groups reported improved diet quality at the end of the study. Grocery participants had greater increases in knowledge (mean [SD] change = 5.7 [6.1] points) than clinic participants (mean [SD] change = 3.2 [4.0] points) ( P  = 0.04). Participants enjoyed the store‐based sessions. Grocery store‐based visits offer a promising approach for dietary counselling.